Continental Patterns of Phenotypic Variation Along Replicated Urban Gradients: A Mega‐Analysis - M. J. Thompson; J. G. A. Martin; C. Biard; J. Bleu; C. J. Branston; P. Capilla‐Lasheras; N. J. Dingemanse; D. M. Dominoni; M. Eens; T. Eeva; K. L. Evans; C. Isaksson; et al. (Ecology Letters, 2025)
Individual variation among and within natural populations can have eco‐evolutionary implications by, for example, affecting species interactions or evolutionary potential. Urban systems present a unique opportunity to evaluate how environmental change shapes variation since urban phenotypic differentiation is widely documented on contemporary timescales. We introduce and test three hypotheses to determine how urbanisation affects phenotypic variation at different population levels. Combining 21 long‐term datasets in a mega‐analysis approach, we synthesise how urbanisation impacts variation in tarsus length and lay date among and within subpopulations of great and blue tits ( Parus major , Cyanistes caeruleus ) at a continental scale. Our synthesis reveals that urbanisation is associated with increased phenotypic variation within subpopulations by 11% on average, and by as much as 25% across the species and traits examined. We also find some evidence (for tarsus length in great tits) that urbanisation increases differentiation between subpopulations. We did not, however, find that urbanisation increases differences between subpopulations in their within‐subpopulation variation. Our synthesis provides novel insights into how urban contexts impact individual diversity at different spatial scales and we highlight future directions that could establish the genetic and environmental effects that underlie these continental patterns of urban phenotypic variation.